Predictors of microfinance sustainability: Empirical evidence from Bangladesh - Maeenuddin; Sha'ari Abd Hamid; Mochammad Fahlevi; Annuar Md. Nassir; Padzil Mohd Hashim (Cogent Economics & Finance, 2023)
Poverty reduction and sustainability are the two major issues in achieving sustainable development. Microfinance emerged as an essential catalyst for socioeconomic development and financial inclusion to reduce poverty. MFIs cannot meet their primary objective of poverty reduction if they are not sustainable financially. With the theoretical support of the Profit Incentive theory, this paper examines the financial sustainability of microfinance providers (MFPs) in Bangladesh. A financial sustainability index (FSI) is developed by using Principal Component Analysis (PCA). This study analyzes the data using two-step system GMM from 2006 to 2018 collected from the MIX market of the World Bank. The results show that loan size, number of borrowers, percentage of women borrowers, and inflation significantly impact FSI positively. Organizational structure, liquidity, leverage, cost per borrower and GDP have significant negative impacts on the financial sustainability of the microfinance sector of Bangladesh. Upon further analysis, the estimates demonstrated that national governance indicators have a negative impact on the relationship between organizational structure, average loan balance per borrower and FSI. Similarly, a stronger national governance reduces (erases) the negative effect of number of borrowers and cost per borrower on FS of MFPs of Bangladesh. This study incorporated all six dimensions of the national governance indicators and developed a new financial sustainability index for measuring the financial sustainability of microfinance providers.
Keywords: 330; Financial sustainability; microfinance; microfinance providers; national governance indicators; sustainability; sustainability index